Analysis of the Waste Management System at Tombro TPS Tunjungsekar Village, Lowokwaru District, Malang City, East Java - fifi damayanti; Yurnalisdel Yurnalisdel; Evabius Venus Darnia (Journal of Evrímata: Engineering and Physics, 2025)
Currently, the Temporary Waste Collection Point (TPS Tombro) faces challenges in implementing a waste processing system based on the 3R principle (Reduce, Reuse, Recycle). While there are sorting facilities, the inorganic waste sorting largely depends on scavengers, and there is no organic waste processing. This research aims to analyze the waste management system at TPS Tombro, focusing on its infrastructure, supporting facilities, and capacity to accommodate waste from the surrounding area. Data collection was conducted through interviews, field observations, and waste transport surveys. The results show that although some of the infrastructure and facilities are underutilized, TPS Tombro can still manage the waste generated in its service area without significant accumulation. The study also provides quantitative data on the daily waste volume and compares the capacity of TPS Tombro with the generated waste. The analysis reveals potential areas for improving the waste management process, ensuring greater efficiency and sustainability